Bone Metastases in Nasopharyngeal Carcinoma - Ni Ketut Susilawati; Hamsu Kadriyan (TALENTA PUBLISHER, 2020)
Introduction: The incidence of bone metastases is as much as 20% of all distant metastases in nasopharyngeal carcinoma (NPC). However, the publication regarding bone metastasis is limited. Case Report: Reported a 58-year-old male patient with a mass on the right upper jugular neck lymph node. According to history taking, physical examination, radiology, and histopathology work up, concluded that the patients were established as nasopharyngeal cancer with the thoraco-lumbal bone metastasis. The physician was starting the chemotherapy; however, due to the advanced stage, this patient was death after the second chemotherapy. Conclusion: In this article presented a nasopharyngeal carcinoma case with bone metastases that have been diagnosed with stage IV B nasopharyngeal carcinoma. This article also described the pathophysiology, diagnosis, and treatment of bone metastases in nasopharyngeal carcinoma.